MONITORING AS A TOOL OF ASSESSMENT IN ENGLISH LANGUAGE CLASSES - Qodirov Olim (Bright Mind Publishing, 2026)
Assessment in English Language Teaching (ELT) is often thought to be connected with tests and examinations. However, modern communicative and learner-cantered approaches highlight the importance of formative assessment used in everyday classroom practice. One of the most underestimated but powerful instruments of such assessment is teacher monitoring. Commonly viewed as a classroom management technique, monitoring in fact provides teachers with real-time diagnostics information about learners’ language use, task understanding, participation, and interaction. This article examines monitoring as a formative assessment tool in English language classrooms. Drawing on methodological literature, classroom observation, and reflective teaching practice, the paper shows how purposeful monitoring enables teachers to collect authentic evidence of learning, provide timely feedback, use different instruction techniques, and foster learner autonomy.
Keywords: Monitoring, assessment, formative assessment, ELT, feedback, classroom observation, learner autonomy.